Neuronal NMNAT2 Overexpression Does Not Achieve Significant Neuroprotection in Experimental Autoimmune Encephalomyelitis/Optic Neuritis - Liu, Pingting; Huang, Haoliang; Fang, Fang; Liu, Liang; Li, Liang; Feng, Xue; Chen, Wei; Dalal, Roopa; Sun, Yang; Hu, Yang (Frontiers in Cellular Neuroscience, 2021)
Optic neuritis, inflammation and demyelination of the optic nerve (ON), is one of the most common clinical manifestations of multiple sclerosis; affected patients suffer persistent visual symptoms due to ON degeneration and secondary retinal ganglion cell (RGC) death. The mouse experimental autoimmune encephalomyelitis (EAE) model replicates optic neuritis and significant RGC soma and axon loss. Nicotinamide mononucleotide adenylyltransferases (NMNATs) are NAD+-synthetic enzymes that have been shown to be essential for axon integrity, activation of which significantly delays axonal Wallerian degeneration. NMNAT2, which is enriched in axons, has been proposed as a promising therapeutic target for axon injury-induced neurodegeneration. We therefore investigated whether activation of NMNAT2 can be used as a gene therapy strategy for neuroprotection in EAE/optic neuritis. To avoid the confounding effects in inflammatory cells which play important roles in EAE initiation and progression, we used an RGC specific promoter to drive the expression of long half-life NMNAT2 mutant in mouse RGCs in vivo. However, optical coherence tomography in vivo retina imaging did not reveal significant protection of the ganglion cell complex; and visual function assays, pattern electroretinography and optokinetic response also showed no improvement in mice with NMNAT2 overexpression. Postmortem histological analysis of retina wholemounts and semithin sections of ON confirmed the in vivo results: NMNAT2 activation in RGCs does not provide significant neuroprotection of RGCs in EAE/optic neuritis. Our studies suggest that a different degenerative mechanism than Wallerian degeneration is involved in autoimmune inflammatory axonopathy and that NMNAT2 may not be a major contributor to this mechanism.